MAULANA MUHAMMAD ALI'S INTERPRETATION OF THE STORY OF ISA/JESUS - Roma Wijaya; Muta'allim Muta'allim (Institut Agama Islam Negeri (IAIN) Ponorogo, 2023)
The concept of birth is understood by Maulana Muhammad Ali as the result of Maryam's marriage to Yusuf. As for the crucifixion, Ali acknowledged the truth of this fact but denied that Jesus died on the cross but died naturally in the Kashmir area. This research is qualitative with its material object, namely the interpretation of Maulana Muhammad Ali in the context of the commentary of The Holy Qur'an. This article uses Gadamer's hermeneutic theory. The results of this study are historical effect or historical influence reveals that Maulana Muhammad Ali experienced a phase of British colonialism which did not only carry out political and economic missions but also aimed at Christian missionaries and friction with Hindu groups. Ali's pre-understanding was dominated by Ahmadiyah ideology. Fusion of horizons raises the assimilation of horizons owned when Maulana Muhammad Ali produced his interpretation, namely that Isa was not claimed to have died during the crucifixion. The application of the interpretation of the story of Isa has a moral message, namely the existence of the same perception of the role model of Isa because he was born from the holy womb of Maryam.